The Mediation Effect of Self Confidence In The Effect of Self Efficacy on The Creativity of Msme Actors In East Java - Rahma Ulfa Maghfiroh; Sudarmiatin Sudarmiatin; Agus Hermawan (Dinasti Review, 2022)
The participation of micro, small, and medium-sized enterprises (MSMEs) is one of the elements that can either contribute to or detract from the rate of economic growth in Indonesia. This study incorporates responses from 194 small and medium-sized businesses located within the province as its sample. This study made use of the purposive random sample approach for its data collection, and primary data was the type of data that was analyzed over the course of the study. Structural Equation Modeling (SEM), along with a Partial Least Squares (PLS) approach, is the technique for doing data analysis. According to the findings, a person's level of self-efficacy and self-confidence had a constructive and important bearing on their creative output. Furthermore, the findings indicate that self-confidence is able to operate as a mediator between the influence of self-efficacy and the creative output of MSME actors in East Java.